The Quaternary Sedimentology and Stratigraphy of Small, Ice-Proximal, Subaqueous Grounding-Line Moraines in the Central Niagara Peninsula, Southern Ontario - Menzies, John (Géographie physique et Quaternaire, 2001)
abstractA series of small moraine ridges in the central Niagara Peninsula, southern Ontario, were investigated in order to understand the impact the retreating Lauren- tide Ice Sheet had on this area of Canada, in terms of the Quaternary sedimentology, stratigraphy and geomorphology. As the ice retreated from the Lake Erie Basin, the area was simultaneously inundated by a series of glacial lakes. The only surface expression of this retreat phase of the ice sheet are suites of small moraine ridges. The morphology, stratigraphy, and sedimentology of these ridges indicates that they were probably formed, over a short period of time, in an ice proximal sub- aqueous environment at the rapidly retreating grounding-line margin of the ice sheet. The sediments reveal a stratigraphy that indicates an association of grounded ice sheet and sub- aqueous marginal conditions.